Availability of assets and livelihood strategies of school dropout teenage mothers in Adaklu District, Ghana - Prisca Ama Anima; Anthony Mwinilanaa Tampah-Naah (Cogent Social Sciences)
The consequences associated with being a teenage mother can be overwhelming, especially when dreams of completing school and getting a lucrative job are shattered. Nevertheless, teenage mothers who are school dropouts gather resources available that aid them in securing livelihood activities for themselves. The aim of this research is to identify assets available to school dropout teenage mothers and how they are using these assets to secure some form of livelihood activities that help lessen the vulnerabilities associated with being a teenage mother. Data was collected from 45 teenage mothers and 17 opinion leaders in the Adaklu District of Ghana using in-depth interviews and focus group discussions. The findings revealed that although teenage mothers depend on various assets, natural assets (land) were the most asset for teenage mothers since most of them were into farming activities. Some of the teenage mothers indulged in off-farm activities like selling charcoal, gari processing, and deshelling of groundnuts to avoid falling deeper into livelihood insecurities. It was recommended that the district assembly should collaborate with NGOs and other institutions to train targeted teenage mothers in self-employable skills like soap making, bead making, and catering services to ease their financial stress. These measures might possibly pave the way for them to re-enter the schooling system.